Membangun Citra Positif Sekolah Melalui Pelayanan Manajemen dan Penguatan Kinerja Guru : Studi Kasus di SDIT Al-Hidayah Cibinong Bogor - Priyanto Priyanto; Nurhasan Nurhasan (Jurnal Manajemen dan Ilmu Administrasi, 2026)
This study aims to deeply examine the process of building a positive school image through two main pillars: management service and strengthening teacher performance. A positive school image is a strategic asset that influences public trust and the interest of prospective students. Previous studies tend to be quantitative, focusing on the influence of these variables on student satisfaction (Baeruma et al., 2025) or using a marketing approach (Hanafi et al., 2023). This qualitative research is present to fill this gap by exploring the strategy, implementation, and meaning behind the school's efforts to integrate the quality of management service and the improvement of teacher performance as a unified process of image formation. Using a qualitative case study method, this research seeks to answer how schools formulate and implement excellent management services and sustainable teacher performance strengthening programs, and how these two aspects synergistically contribute to the formation of a positive image in the eyes of stakeholders. The findings of this study are expected to provide a practical and theoretical model for educational practitioners in managing schools as service institutions oriented towards quality and image.